Microencapsulation of self-healing agents containing a fluorescent dye - J. K. Lee; H. H. Noh (eXPRESS Polymer Letters, 2013)
Two different self-healing agent candidates, endo-dicyclopentadiene (endo-DCPD) and 5-ethylidene-2-norbornene (ENB), containing a fluorescent dye surrounded by a melamine–urea–formaldehyde (MUF) shell were microencapsulated by in-situ polymerization and the resulting microcapsules were characterized in this work. The microcapsules showed a narrow size distribution with a spherical shape and rough outer and smooth inner surfaces for both healing agent systems. Shell thicknesses of the microcapsules were ~880±80 nm for endo-DCPD and ~620±60 nm for ENB. The incorporation of a fluorescent dye as tracer into self-healing agents did not disturb the formation of microcapsules. The release of self-healing liquid into the induced crack from ruptured microcapsules in an epoxy coating layer was observed using a fluorescence microscopy. The use of a fluorescent dye is very effective in the observation of a damage site.